Influence of temsirolimus on antidiabetic effect of sitagliptin in experimental animal - Jamal, Roohi; K Suresh, D.; S Khalid, Md (International Journal of Pharmacology and Toxicology, 2018)
The present study was carried out to evaluate the drug interaction between an antihyperglycemic agent and anticancerous drug,In healthy and Dexamethasone induced diabetic rats. The blood samples were collected up to 24 h and blood glucose level was estimated. In healthy albino rats Pretreatment with Temsirolimus (6.75 mg/kg for seven days) has significantly altered the onset of hypoglycemia (15.50+1.47 to21.40±.54), p< 0.001 at the 2nd hour significantly enhanced the peak hypoglycemia (29.70+.60 %) before treatment to (44.47+1.21 %) after treatment(p
Keywords: Influence of Temsirolimus; Antidiabetic Effect of Sitagliptin; Dexamethasone and Drug Interaction.